Comparing Bayesian methods to estimate the failure probability for electronic systems in case the life time data are not available - عبد الوهاب, بيداء اسماعيل (Journal of Economics and Administrative Sciences, 2014)
In this research, we find the Bayesian formulas and the estimation of Bayesian expectation for product system of Atlas Company.  The units of the system have been examined by helping the technical staff at the company and by providing a real data the company which manufacturer the system.  This real data include the failed units for each drawn sample, which represents the total number of the manufacturer units by the company system.  We calculate the range for each estimator by using the Maximum Likelihood estimator.  We obtain that the expectation-Bayesian estimation is better than the Bayesian estimator of the different partially samples which were drawn from the product system after  it checked by the technical staff of the company and by using the range as statistical criterion.